OPTIMALISASI FUNGSI PENGORGANISASIAN (ORGANIZING) DALAM PENGELOLAAN KEGIATAN SISWA DI SMK MAKARYA 1 JAKARTA - Ade Fikri Mustofa; Dimas Abdurahman; Nurwadipa Anggara Putra; Ahmad Nurhadi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service program (Pengabdian kepada Masyarakat) was conducted at SMK Makarya 1 Jakarta with the aim of optimizing the implementation of the organizing function within the institution. The background of this activity is the limited understanding and practice of the organizing function among students and student-organization administrators, which leads to unclear division of tasks, weak coordination between units, and the absence of a properly documented organizational structure. The implementation method consisted of lectures, interactive discussion, group simulation, and direct mentoring on the concepts and practice of organizing, involving 32 participants and 12 student facilitators from the Management Study Program of Universitas Pamulang. The results indicate a significant improvement in participants' understanding of organizing principles, reflected in their ability to design a clear division of tasks, build inter-unit coordination, and draft a simple organizational structure chart. This activity is expected to contribute to the sustainable strengthening of organizational management capacity at the partner institution.